พฤติกรรมผู้บริโภคในกรุงเทพมหานครในการซื้อชุดชั้นในสตรีจากห้างสรรพสินค้า - พิมพ์ณรัตน์ เจริญมากสุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The objective of this independent study was to study the behavior of customer in Bangkok towards purchasing women underwear from department store. The population was 300 people who were women aged 15 - 59 years old living in Bangkok, had used or bought women’s lingerie. The data was collected from questionnaire and analyzed by descriptive statistics such as frequency, percentage, and mean. The results of the study showed that the questionnaire respondents were mostly aged between 35 - 44 years old, single with bachelor degree. Most of them were employees with average salary of 10,001 - 20,000 baht. Almost of respondents intentions to buy underwear don’t plan in buying but if they were satisfy its design, they would buy suddenly. And they liked to buy same design both of brassiere and underwear. They did the purchase of brassieres 1 - 3 times per year. Most of respondents bought sport bras. They spent average 251 - 500 baht per piece and bought 3 - 4 pieces per purchase brassiere in once time. And they bought brassieres from high grade department store. For underwear, they bought 1 - 3 times per year. They preferred to full body panty. They spent average 101 - 250 baht per piece and bought 3 - 4 pieces per once time. And they preferred to buy underwear from high grade department store. The most satisfy brand is Wacoal. And they could buy all the time that they were convenience. Mostly of respondents gave cause of purchasing underwear was the shape which fit and support to their breast and body. They knew information about underwear and distribution channel from themselves and they made decision to buy underwear by themselves. The most important thing in making decision to buy was quality. The marketing mix factors that affected buying behavior at the high level were ranked in the following order: Product factor that affect to the decision to buying is durable and using long time. Price factor that affect to the decision to buying is price to be suitable with quality of product. Place factor that affect to the decision to buying is location of store to be convenient for visiting. And marketing promotion factor that affect to the decision to buying is staff can advise, give knowledge and answer the question about lingerie to customer very well.